Neuronal Pentraxin 1 Negatively Regulates Excitatory Synapse Density and Synaptic Plasticity - Figueiro-Silva, Joana (J Neurosci, 2015)
In mature neurons, the number of synapses is determined by a neuronal activity-dependent dynamic equilibrium between positive and negative regulatory factors. We hypothesized that neuronal pentraxin (NP1), a proapoptotic protein induced by low neuronal activity, could be a negative regulator of synapse density because it is found in dystrophic neurites in Alzheimer's disease-affected brains. Here, we report that knockdown of NP1 increases the number of excitatory synapses and neuronal excitability in cultured rat cortical neurons and enhances excitatory drive and long-term potentiation in the hippocampus of behaving mice. Moreover, we found that NP1 regulates the surface expression of the Kv7.2 subunit of the Kv7 family of potassium channels that control neuronal excitability. Furthermore, pharmacological activation of Kv7 channels prevents, whereas inhibition mimics, the increase in synaptic proteins evoked by the knockdown of NP1. These results indicate that NP1 negatively regulates excitatory synapse number by modulating neuronal excitability and show that NP1 restricts excitatory synaptic plasticity.